The crime of human trafficking (A comparative legal study between Egypt and Saudi Arabia) - Zekry, Reem Gomaa (Journal of Economic, Administrative and Legal Sciences, 2025)
Human trafficking is one of the most serious global crimes that has become increasing due to wars and the exodus of many refugees from their afflicted country to other countries. This is in addition to the development of technological means, which has greatly contributed to trapping victims in the nets of various criminal organizations. And even the ease of concealing forensic evidence that might convict the perpetrators. This crime has many types, including prostitution, organ trade, sexual exploitation of children, recruiting them in areas of armed conflict, trafficking in them, etc., as well as its victims, most of whom are women and children. All of this entails precautionary measures from those responsible for developing and implementing various laws, as well as countries coming together and establishing cooperation agreements between them to eliminate criminal organizations, which are often distributed among three countries as a trader, broker, and buyer. One of these countries are Egypt and the Kingdom of Saudi Arabia. This is what we will address in this research.